Metabolic Syndrome in the Spectrum of Hair Grayness - Al-Hamamy, Hayder R.; Al-Mashhadani, Sabeeh; Salman, Husam A.; Abdullah, Zaid F. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: hair graying is an aging sign; it is associated with ischemic heart disease. Metabolic syndrome often associates with increased risk for atherosclerotic arterial disease.Objective: To test retrospectively the association between onset of hair graying and risk of metabolic syndrome.Methods: Four hundred and eighty one gray hair individuals, with no history of atherosclerotic diseases were included. The individuals have been divided into metabolic syndrome and control groups. Each individual was asked about the decade (2nd-6th) of onset of hair grayness.Results: Patients with metabolic syndrome had peak onset of hair grayness in the 4th decade which was statistically higher than the control group (p values= 0.045). While the peak onset in the control group was in the 5th decade which was different from the metabolic syndrome group (p-value = 0.024). The difference was not significant in the 2nd, 3rd and 6th decades of life.Conclusion: Patients with metabolic syndrome had an earlier age of onset of hair grayness.